A Direct Three‐Component Reaction for the Isolation of a Nonanuclear Iron(III) Phosphonate. Issue 26 (30th July 2014) - Goura, Joydeb; Liu, Junjie; Goddard, Paul; Chandrasekhar, Vadapalli
Abstract: The synthesis, structure, and magnetism of a nonanuclear iron(III) phosphonate, [Fe9 III (μ3 ‐O)4 (O3 PC5 H9 )3 (O2 CCMe3 )13 ]· (EtOH)0.5 · (Et2 O)0.5 (1 ), is described. Compound1 was obtained in the direct reaction of anhydrous ferric chloride, cyclopentylphosphonic acid, and pivalic acid in the presence of triethylamine. Compound1 possesses a distorted icosahedral structure; nine of the vertices are occupied by Fe III, whereas three others are occupied by the phosphorus atoms of the cyclopentylphosphonate ligand. Mössbauer spectroscopy of1 confirms the presence of high‐spin Fe III . Low‐temperature magnetic studies reveal the presence of strong antiferromagnetic coupling between the Fe 3+ ions. Abstract : The reaction of anhydrous ferric chloride with cyclopentylphosphonic acid and pivalic acid in the presence of triethylamine at room temperature afforded a nonanuclear iron(III) phosphonate. It possesses a cage structure with a distorted icosahedral core. Mössbauer studies confirm high‐spin Fe III, whereas magnetic measurements suggest strong antiferromagnetic couplings between the Fe 3+ ions.